DSS for Mobile-Based Determination of the Quality of Gayo 1 Coffee Seedlings by Combining the AHP-WP Method - Mia Nurjannah; Samsudin Samsudin; Muhammad Dedi Irawan (IJAIT (International Journal of Applied Information Technology), 2021)
Determining the quality of Gayo 1 coffee seeds with manual calculations can affect time efficiency because manual calculations often result in inconsistent and time-consuming calculations. A decision support system is needed to determine the quality of Gayo 1 coffee seeds with consistent and accurate calculations and processed through computational speed. Applying the AHP-WP method can determine the quality of coffee seeds of the Gayo 1 variety at IP2TP Gayo. The discussion that becomes the focus is the application of the AHP method to determine the weight of the coffee seed criteria. The resulting weight can be continued in the calculation of the WP method to determine the quality of the Gayo 1 coffee seed based on the alternative preference value or vector S. The results of the study provide information regarding the quality of coffee seeds that have been tested for quality.